1983
DOI: 10.1007/bf02341649
|View full text |Cite
|
Sign up to set email alerts
|

Die Beurteilung des Suizidrisikos

Abstract: Before committing a suicidal act, many people consult a doctor because of somatic or functional complaints. Most of them do not express their suicidal thoughts, unless they are asked direct questions. The taking of a thorough history, possibly supplemented by information from relatives or friends, is the safest basis for an optimal assessment of the suicide risk. Predisposing factors are: 1. Depression 2. Alcohol or drug dependence 3. Old age and loneliness 4. Warnings or threats of suicide 5. Past suicide att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…According to the literature, important factors in this connection are depression, hopelessness, fear, and phobia [Wolfersdorf et al, 1990; De Anda & Smith, 1993; Rudd et al, 1995; Simonds et al, 1991; Keller & Wolfersdorf, 1993; Keller, 1996]. It has also been shown that many patients who have attempted suicide prefer to blame somatic ailments for their distress rather than seek psychiatric help [Haenel, 1983]. Therefore, somatization would seem to be another attribute of this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, important factors in this connection are depression, hopelessness, fear, and phobia [Wolfersdorf et al, 1990; De Anda & Smith, 1993; Rudd et al, 1995; Simonds et al, 1991; Keller & Wolfersdorf, 1993; Keller, 1996]. It has also been shown that many patients who have attempted suicide prefer to blame somatic ailments for their distress rather than seek psychiatric help [Haenel, 1983]. Therefore, somatization would seem to be another attribute of this patient group.…”
Section: Introductionmentioning
confidence: 99%